Global determinants of Malaysia government bond - Ahmad Al Izham, Izadin (2021)
This study seeks to investigate the global determinants of Malaysia government bond yield using monthly data from 2008 to 2019. This study employs the Johansen cointegration test and Vector Error Correction Model (VECM) to test the existence of long-run and short-run equilibrium within Malaysia government bond yield using the VIX index as a proxy for investor sentiment, USDMYR representing Malaysia currency, oil price and gold price. The results of the study suggest that investor sentiment and gold price have significant relationships with the Malaysia government bond yield in the long run while oil price, currency, investor sentiment and gold price have a short-run relationship with Malaysia government bond. However, only VIX index and oil price granger casual Malaysia government bond yield in the short run. This research will help explain the domestic bond market yield movement using more frequent daily data point like VIX index, currency, oil price and gold price compared to macroeconomic data like GDP or other Malaysia’s fiscal data which are only available on a monthly or quarterly basis. This research will also add to the literature study on the determinants of the Malaysia Government bond which allow regulators to design policies in improving the efficiency of the bond market in Malaysia